Beneficios de la biofumigación en los cultivos de tomate (Solanum lycopersicum L.) - Alvarez Burgos, Moises Isaac (2022)
The tomato (Solanum lycopersicum L.) is one of the most important vegetables grown around the world, China stands out as its main producer with 860 tons, the United States is the country that imports this vegetable the most, while Mexico is the country that imports the most exports it, allocating most of it to the United States market, in Ecuador there are 3 thousand hectares of tomato, the production is approximately 62 thousand tons per year, in tomato crops pest control has been supported by traditional methods such as the use of pesticides of synthetic origin, under the excuse of their versatility and their way of acting in the control of different organisms that affect the crop in a single application or their easy storage, in some cases, their repeated use has caused some pests have become resistant to these chemical control products, biofumigation is an alternative method for controlling pests that are affecting a crop, its process takes place When residues with beneficial properties for the defense of the crop go through a vaporization phase, generating a natural compound called isothiocyanate, which has a powerful antifungal activity, some of the physical and chemical advantages in the application of biofumigation are set out below: it increases the physical properties of the soil by binding it and forming bonds with reactive surfaces of mineral particles, which allows them to form more stable aggregates in the soil, thus supporting the soil structure, increases the water holding capacity of the soil by adding pores of larger diameter, which requires less energy to retain water and is more easily absorbed by plants, in addition, increased water penetration extends hydraulic conductivity.